Functional probes for the diagnosis and treatment of infectious diseases - Zhijin Fan; Yan Liu; Yuyun Ye; Yuhui Liao (Aggregate)
Abstract Infectious diseases present significant challenges to global health, thereby extensively affecting both human society and the economy. In recent years, functional probes have demonstrated remarkable potential as crucial biomedical media for the research and treatment of infectious diseases. Their applications in the realm of infectious diseases include pathogen detection, exploration of biological mechanisms, and development of anti‐infective drugs. This review provides a concise introduction to the severity, classification, and pathogenesis of infectious diseases. Subsequently, we examined the distinctiveness and design strategies of functional probes for diagnosing and treating infectious diseases, shedding light on their design rationale using typical examples. We discuss the current status and challenges associated with the clinical implementation of functional probes. Furthermore, we explored the prospects of using these probes for the diagnosis and treatment of infectious diseases. This review aims to offer novel insights into the design of diagnostic probes for infectious diseases and broaden their applications in disease treatment.